2019
DOI: 10.1177/0011128719850497
|View full text |Cite
|
Sign up to set email alerts
|

Military Service: A Pathway to Conformity or a School for Deviance?

Abstract: Military service has been shown to affect individuals’ criminal and deviant tendencies. Studies on military service and deviance, however, has generally focused on combat veterans, utilized cross-sectional data, and ignored the potentially differential impact of military service based on sociodemographic variations. Utilizing the Add Health data and multilevel growth curve modeling, this study intends to reveal (a) trajectories of deviance from adolescence through adulthood, (b) whether military service in you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Limited evidence has also found that men who enter the military score lower when testing for traits like openness, neuroticism, and agreeableness-and demonstrate decreasing levels of agreeableness compared to civilians years later after training, indicating the presence of both selection and socialization processes (Jackson et al, 2012). However, in several longitudinal studies, military service has been shown to reduce a variety of criminal behaviors over time, including aggressive offending, property crime, and drug use, though this effect may depend on the group, cohort era, or active duty status (Baktir et al, 2020; see also 106 Armed Forces & Society 49(1) Bouffard, 2005;Orak & Walker, 2021;Snowden et al, 2017;Teachman & Tedrow, 2016). While disentangling the "transformative" ability of military culture is beyond the scope of this article, future work should consider the possibility of selection effects with the awareness that those who are arrested and sentenced to prison remain different as well.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence has also found that men who enter the military score lower when testing for traits like openness, neuroticism, and agreeableness-and demonstrate decreasing levels of agreeableness compared to civilians years later after training, indicating the presence of both selection and socialization processes (Jackson et al, 2012). However, in several longitudinal studies, military service has been shown to reduce a variety of criminal behaviors over time, including aggressive offending, property crime, and drug use, though this effect may depend on the group, cohort era, or active duty status (Baktir et al, 2020; see also 106 Armed Forces & Society 49(1) Bouffard, 2005;Orak & Walker, 2021;Snowden et al, 2017;Teachman & Tedrow, 2016). While disentangling the "transformative" ability of military culture is beyond the scope of this article, future work should consider the possibility of selection effects with the awareness that those who are arrested and sentenced to prison remain different as well.…”
Section: Discussionmentioning
confidence: 99%
“…One of the significant life transitions that may modify this association is military service, with life-course research demonstrating that joining the military is a major turning point in the life course, significantly altering or redirecting individuals’ life trajectories and behavioral patterns including criminal behavior (Laub & Sampson, 2003; Orak & Walker, 2021; Teachman & Tedrow, 2016). Previous research has indicated that military service may be particularly attractive to individuals who have experienced adverse childhood events (ACEs), including violent victimization, with a study of post-9/11 veterans finding that approximately 44% of female and 25% of male veterans reported being exposed to multiple ACEs (Aaronson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variation in the functions and impacts of military service, as well as individual characteristics of servicemembers over time, research on veterans from different eras, including the post-9/11 period, indicates that military service is a significant turning point in an individual’s life course (Laub & Sampson, 2003; Orak & Walker, 2021; Teachman & Tedrow, 2016). Specifically, military service may lead to significant changes in the life course, such as leaving the past behind to create a new life, a start or increase of supervision and monitoring, and structure and change in routines, all of which aid in the shift of an identity transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, military service may positively influence individuals’ lives by encouraging social independence, providing time away from the stress associated with transitioning to adulthood, offering exposure to a broad range of perspectives, and strengthening bonds with conventional society, all of which may prevent individuals from engaging in deviant or criminal behavior. (Elder, 1999; Orak & Walker, 2019; Sampson & Laub, 1993). Conversely, military service may disrupt individuals’ socialization process, interrupt existing social roles, and teach service-members how to solve their problems aggressively and with weapons (Hakeem, 1946; Sampson & Laub, 1996).…”
Section: Introductionmentioning
confidence: 99%